Journalists in a circular economy: Stakeholders’ engagement in the media discourse on single-use plastics during the COVID-19 pandemic - Krawczyk, Aleksandra; Goc, Alicja; Pellegrini, Airis; Jaguszewska, Natalia; Salas, Brenda Olivos; Bukowski, Michał; Grodzińska-Jurczak, Małgorzata (Heliyon, 2024)
The world faces an alarming plastic waste problem. The volume of plastic waste is rapidly and continuously increasing, mainly due to the single-use plastics overconsumption, whereas its recycling and utilization leave much to be desired. Despite the negative effects of plastic on the environment and public health, the COVID-19 outbreak shifted the public attention away from the environmental issues, potentially giving space for extended lobbyism by interest groups and industry to delay or even prevent legislation to combat plastic pollution. Our study aims to understand how the media discourse on single-use plastic (SUP) in particular, evolves in the course of the pandemic. How it vary across EU Member States? For this purpose, we specifically analyse plastic-related articles in major prestigious daily newspapers published between June 2019 and June 2021 in four EU Member States: Germany, France, Italy, and Poland, as countries with different levels of sustainable transition to form a representative model of an European context. Additionally, between November 2022 and January 2023, we conducted a series of interviews via Google Meet, with journalists who agreed to be asked on the plastic issues they upraised. Our analysis initially covered 1076 articles, out of which 198 articles were rejected due to non-compliance with the subject or repetition, leaving 878 articles forming the database for eventual analysis. Specifically, we outline a key impact of the COVID-19 pandemic followed by a clear evolution on the number of plastic-related articles, on related stakeholder engagement, and the focus on specific SUP items. Moreover, we address a research gap - presenting a media portrait of different types of SUP in more details and highlighting the significance based on several culturally and linguistically very different countries within a single supranational state (EU). A clear trend reversal towards an informed knowledge circulation across the circular economy model of single-use plastics is ultimately essential to develop sustainable solutions to reject the disposable culture, stop the waste of natural resources, and reduce the consumption of oil or gas for plastic production and thus protect the climate.